Survey methods and research. Main psychopathological syndromes - Safonov, D. M.; Сафонов, Дмитро Миколайович (Запорізький державний медичний університет, 2020)
The tutorial provides materials on modern ideas about the survey methods and research of basic psychopathological syndromes in accordance with the requirements of the curriculum program «Psychiatry and narcology» for the 4th year students of International Faculty №2. The authors used modern requirements for teaching, control of theoretical knowledge, skills and practical abilities in the system of credit transfer of educational evaluation. The materials of tutorial should help students to improve their knowledge and skills in the basic methods of diagnosing mental disorders, expand their understanding of the basic psychopathological syndromes. The tutorial is a guide for conducting practical classes in psychiatry and were developed for the first time. Due to the progressive development of psychiatry, changes in the requirements for specialists, this tutorial will not meet the peda